Sinergi Kurikulum Cambridge dan Pendidikan Islam dalam Pengembangan Karakter - Arinda Firdianti; Shoby Any Cahya; Ruly Nadian Sari (Jurnal Budi Pekerti Agama Islam, 2025)
This study aims to analyze the synergy between the Cambridge Curriculum and Islamic Education in fostering students’ character who are faithful, knowledgeable, and globally competitive. The research employed a Systematic Literature Review (SLR) approach, following the PRISMA protocol to trace, screen, and synthesize relevant literature from reputable databases (Scopus, Web of Science, and Google Scholar) within the 2015–2025 timeframe. Out of 142 identified articles, 38 met the thematic and methodological eligibility criteria. The findings indicate that the integration of the Cambridge Curriculum and Islamic Education creates a hybrid educational model that balances global academic achievement with spiritual and moral development. The Cambridge Curriculum provides a framework for 21st-century competencies, while Islamic Education embeds values, manners, and moral accountability. This synergy requires a paradigm shift among teachers, pedagogical innovation, and curriculum policies centered on character formation. The study concludes that character development based on the integration of global curriculum and Islamic values is a strategic pathway to cultivating an excellent and adaptive Muslim generation ready to face global challenges.